COMPANY VALUATION OF PT ASTRA OTOPARTS TBK: USING THE DISCOUNTED CASH FLOW AND RELATIVE VALUATION METHODS - Muttaqin Rizki Putra (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2025)
This study evaluates the valuation and investment potential of PT Astra Otoparts Tbk. (AUTO), a market leader in Indonesia's automotive component industry, using Discounted Cash Flow (DCF) and Relative Valuation approaches. It analyzes AUTO’s historical financial performance and external business factors using PESTEL and Porter’s Five Forces. The DCF method estimates the company’s intrinsic value through future operational earnings, applying Weighted Average Cost of Capital (WACC) and terminal growth rates. Additionally, Relative Valuation compares AUTO’s key financial ratios (P/E, P/B, EV/EBITDA) with industry benchmarks. Results indicate AUTO is undervalued, with its intrinsic value exceeding the market price. Moreover, AUTO’s superior P/E, PBV, and EV/EBITDA multiples highlight its competitive position, making it an attractive investment opportunity